A practical english grammar Exercises 1 - Thomson, A.J; Martinet, A.V (New York, USA Oxford university press, 2009)
For this edition some changes have been made in the text to bring it up to date and five new exercises have been added making a total for both books of 190. the exercises now follow the grammar and they have all been graded. References are to the fourth [1986] edition of the grammar
A clear, comprehensive reference grammar
12
Keywords: English as a second language; English language -- Grammar; English language -- Usage; english language -- Study and teaching